(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Reproductive autonomy confers a women’s decision and controls over, matters related to contraceptive use, pregnancy, and childbearing. Rural women of Bangladesh have very little control to shape up their family with their minimum empowerment and are lagging behind in the practice of use of family planning methods. Objective: To find out the association among rural women’s reproductive autonomy and contraceptive behavior. Materials and Methods: This cross sectional study was conducted among 284 married rural women of reproductive aged in Mohammadpur upazilla, Magura district of Bangladesh from June 2016 to December 2016 selected through simple random sampling. Mixed method approach was introduced for data collection through face to face interview using pretested questionnaire and focused group discussion. Results: Mean age of the respondents was 26.5±5.7 years with the range of 17 to 45 years. Average monthly family income was 12,561 Taka where majority of the respondents were housewives (83.8%). Education status above primary level was recorded in 23.6%. Early marriage was highly prevalent (77.5%) and mean age of marriage was 17.2±1.7 years. Mean parity was 2.3 per woman. Only 31% of the respondent found to have well reproductive autonomy. Contraceptive use was prevalent in 61.9% of the respondents and only educated women seen to have chance to participate in family planning decision-making. Male participation in contraceptive use was negligible but still men were in main role to give it the final shape to decide about family planning. Women’s reproductive autonomy found to be significantly associated with their contraceptive behavior (p<0.05). Educational status of the women and age gap with the spouse were significantly associated with their reproductive autonomy (p<0.05). Conclusion: Gender issues were prominent in family planning in rural community and rural women accepted the gender disparity in silence. Policy makers and family planning stake holders should put maximum endeavor to improve women’s reproductive autonomy to strengthen their negotiating capacity in fertility control. JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 30-34